Development and evaluation of simulation based neurosurgery curriculum. Pilot study at the Poznan University of Medical Sciences. - Sokół, Bartosz; Jankowski, Roman; Więckowska, Barbara; Gąsiorowski, Łukasz; Czekajlo, Michael (Journal of Medical Science, 2017)
Introduction. Neurosurgical emergencies are complex tasks. The current learning environment limits students’ ability to manage acute neurosurgical emergencies due to legal and safety concerns. Simulation provides an opportunity to participate in the care of neurosurgical emergencies and develop clinical decision making skills. Aim. We aim to determine whether neuroscience simulation curriculum improves student ability to: manage a critically ill patient, recognize neurosurgical emergencies, to assess how stress tolerance affects experience during simulations and effectiveness of students performance. The third objective is to develop a tool for student assessment.Material and Methods. The simulation was performed on SimMan 3G Human Patient Simulator (Laerdal Medical). Scenarios included common neurosurgical emergencies. Students were assessed before and after the course by completing a Likert type questionnaire. Response data was analysed using Cronbach’s reliability for Likert-type response data  and Spearman's monotonic correlation. Results. 60 students of fifth and sixth year of medical studies attended the course. 39 students of them replied to the questionnaire. The simulated clinical experience was positive and it improved their knowledge about neurosurgical emergencies. There was an improvement in their confidence. Improvement in individual and team performance was also observed.Conclusions. Neurosurgical simulations improve students` ability to recognize neurosurgical emergencies. The level of stress related to simulation is important factor of the education process and should be reduced to improve students’ development. Our questionnaire is an effective tool for assessment of students experience during clinical simulations.
Keywords: neurosurgery; simulation; education; medical students